2017
DOI: 10.1002/acr.23213
|View full text |Cite
|
Sign up to set email alerts
|

Population‐Based Study of Changes in Arthritis Prevalence and Arthritis Risk Factors Over Time: Generational Differences and the Role of Obesity

Abstract: Objective. To investigate cohort effects in arthritis prevalence across 4 birth cohorts: World War II (born 1935-1944), older and younger baby boomers (born 1945(born -1954(born and 1955(born -1964(born , respectively), and Generation X (born 1965(born -1974, and to determine whether birth cohort effects in arthritis prevalence were associated with differences in risk factors over time or period effects. Methods. Analysis of biannually collected data from the longitudinal Canadian National Population Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Recent reports have suggested a marked increase in total knee replacement utilization, especially in the population 45–64 years of age, that has outpaced the increasing rate of obesity in the same age group . Another study demonstrated higher arthritis prevalence in more recent birth cohorts, compared to previous generations of the same age, partly due to changing patterns of obesity in relatively younger populations . Individuals younger than 65 years of age may perceive arthritis as a condition affecting only the elderly and thus may visit a health professional less often or may ignore occasional joint symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested a marked increase in total knee replacement utilization, especially in the population 45–64 years of age, that has outpaced the increasing rate of obesity in the same age group . Another study demonstrated higher arthritis prevalence in more recent birth cohorts, compared to previous generations of the same age, partly due to changing patterns of obesity in relatively younger populations . Individuals younger than 65 years of age may perceive arthritis as a condition affecting only the elderly and thus may visit a health professional less often or may ignore occasional joint symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic characteristics, health behaviour, obesity and chronic diseases (e.g. hypertension, heart disease and digestive disease) were found to be significant risk factors of arthritis (Blagojevic et al, 2010;Sugiyama et al, 2010;Li et al, 2015;Badley et al, 2017). A study conducted in China suggested that age, gender, physical exercise and cardiovascular disease were associated with arthritis in adulthood and old age (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, approximately one in five women and one in seven men will have a TKA [1], and one in eight women and one in ten men will have a THA [2]. The increasing risks are largely attributed to the aging population [1, 35], and increasing obesity [1, 4, 6]. In 2017, 91,857 primary TKA and THA procedures were undertaken in Australia; most (TKA 70%; THA 67%) occurred in the private sector [7].…”
Section: Introductionmentioning
confidence: 99%